Sprint diagnostic with GPS and inertial sensor fusion - Mertens, J. C.; Boschmann, A.; Schmidt, M.; Plessl, C. (Sports Engineering, 2018)
The purpose of this research was to develop a wearable, low-cost prototype based on real-time kinematic GPS and a microelectromechanical inertial measurement unit to measure the sprinting velocity of an athlete. The software package RTKLIB was used to calculate the RTK-GPS positions and different Kalman filters were implemented to provide a loosely coupled sensor fusion. With this setup, we performed empirical studies to determine whether the velocities obtained by this novel approach are sufficiently accurate for a performance orientated training. Therefore, field tests for 30- to 400-m sprint distance were conducted with simultaneous measurements with different reference systems, such as a laser device or timing gates. The evaluation revealed a correspondence between prototype and reference systems with distance and timing errors of ±2% and high correlations for the velocities (R = 0.996, P <0.001) for 68 % of the trials. However, for remaining 32 % of the trials no acceptable performance parameters could be obtained due to GPS problems. Overall, the developed prototype showed great potential and might allow closing the gap between the accuracy and flexibility of the established reference systems as soon as its susceptibility to GPS problems is lowered.